Analýza objemových změn cementových kompozitů s ohledem na optimalizaci dávkování jemných složek - Meruňka, Milan (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Diplomová práce se zabývá stanovením vlivu maximální hutnosti cementové matrice na objemové změny betonu, vlivu rozdílných příměsí či jejich kombinací na vývoj hydratačních teplot a na odlučivost vody z betonu. V teoretické části práce jsou popsány jednotlivé druhy objemových změn betonů, vliv jednotlivých vstupních složek a minerálních příměsí na odlučivost vody, vývoj hydratačního tepla a mikrostrukturu betonu. Experimentální část je zaměřena na sledování nejen objemových změn betonových směsí vyrobených s použitím různých druhů příměsí či jejich vhodné kombinace do stáří 60 dnů zrání, ale také vlivu jejich použití na vybrané mechanické parametry betonu jako jsou pevnost v tlaku, vodotěsnost, nasákavost nebo odlučivost vody z betonu v jeho čerstvém stavu a sledování změn mikrostruktury z dlouhodobého měřítka zrání směsí.

The diploma thesis deals with the determination of the influence of the maximum density of the cement matrix on the volume changes of concrete, the influence of different admixtures or their combinations on the development of hydration temperatures and on the water separation of concrete. The theoretical part describes the various types of volume changes of concrete, the effects of individual input components and mineral admixtures on water separation, hydration heat development and concrete microstructure. The experimental part is focused on monitoring not only the volume changes of concrete mixtures made using different types of admixtures or their suitable combination until the age of 60 days of maturation, but also the influence of their use on selected mechanical parameters of concrete such as compressive strength, concrete in its fresh state and monitoring changes in the microstructure from long-term aging mixtures.
Analysis of volume changes of cement composites with respect to optimizing the dosage of fine components
Keywords: Objemové změny betonu; smrštění betonu; minimální mezerovitost cementové matrice; maximální hutnost cementové matrice; vývoj hydratačních teplot; mikrostruktura betonu…; Volume changes of concrete; shrinkage of concrete; minimum voidsity of cement matrix; maximum density of cement matrix; development of hydration temperatures; microstructure of concrete…